Composition capable of tightening vagina and recovering elasticity and preparation method thereof

By using hydrolyzed collagen peptides of specific molecular weight, composite cross-linking agents, and pH-responsive carrier technology, the problems of low membrane permeability and poor stability of ingredients in vaginal care products have been solved, achieving efficient repair and stability for vaginal tightening and restoration.

CN120939208APending Publication Date: 2025-11-14广州市幽蜜生物科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511274664.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing vaginal care products suffer from problems such as low transmembrane efficiency of ingredients, lack of synergistic mechanism of action, and poor stability of active ingredients, failing to effectively address the repair and maintenance of collagen fiber networks.

Method used

A composition with vaginal tightening and elasticity restoration is formed by using hydrolyzed collagen peptides with a molecular weight of 1800-3800 Da, a complex cross-linking agent, a plant tannin delivery system, and a fibroblast activating factor, through chemical grafting and pH-responsive carrier technology.

Benefits of technology

It achieves precise transmembrane penetration of collagen peptides, dual repair function of cross-linking agents, intelligent controlled release of plant tannins, and efficient activation of fibroblasts, thereby improving the vaginal tightening and recovery effect and the stability of the ingredients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a composition capable of tightening vagina and recovering elasticity and a preparation method thereof, and the composition comprises the following components in parts by mass: 75-130 parts of a collagen structure repairing unit, 25-55 parts of a composite cross-linking agent, 8-35 parts of a fibroblast activating factor and 12-38 parts of a plant tannin delivery body. The problem of membrane permeation is solved through high-activity hydrolyzed collagen peptide, a difunctional cross-linking system is formed by chemical grafting of dermatan sulfate and carboxymethyl beta-glucan, the fibroblast activation efficiency is enhanced by means of a zinc ion mediated polypeptide complexing structure, and the bottleneck in the prior art is remarkably broken through on key indexes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of women's reproductive health care technology, specifically relating to a composition that tightens and restores vaginal elasticity and its preparation method. Background Technology

[0002] The elastic function of the vaginal wall is mainly maintained by the collagen fiber network, elastin, and extracellular matrix. The technical shortcomings of existing commercially available products are concentrated in three aspects: First, the ingredients have low transmembrane penetration efficiency. Most creams use high molecular weight collagen (>50kDa) as a repair agent. For example, a well-known brand adds bovine collagen with a molecular weight as high as 300kDa, which cannot penetrate the squamous epithelium of the vaginal mucosa. Although in vitro tests show that its water absorption rate reaches 300%, in actual application, 93% of the effective ingredients are washed away and metabolized by vaginal secretions within 24 hours.

[0003] Secondly, the mechanisms of action lack synergy. Traditional methods rely on chemical astringents (such as zinc phenolsulfonate) to forcibly contract tissues, which can reduce the diameter of the uterine lining by 0.5-1 mm in the short term, but this leads to mucosal dehydration and dryness. After continuous use for 7 days, the survival rate of lactobacilli decreases by more than 60%, disrupting the normal acidic environment. Other studies have attempted to add estrogen precursors, but their metabolite, estradiol, can be absorbed through the mucosa into the bloodstream, posing a potential risk of abnormal endometrial hyperplasia.

[0004] Thirdly, the active ingredients have poor stability. Natural plant extracts (such as St. John's wort extract, which is commonly used for repair) need to undergo an emulsification stage at temperatures above 60°C during the conventional preparation of creams, resulting in the degradation and inactivation of more than 40% of heat-sensitive ingredients. In a literature-documented accelerated stability test at 40°C, the activity retention rate of Centella asiatica nanoemulsion was only 28% after 90 days.

[0005] To address the aforementioned shortcomings, existing improved technologies still have some limitations: liposome encapsulation can improve the permeability of small molecule peptides, but phospholipid materials are prone to acyl hydrolysis in environments with pH < 4.5, releasing free fatty acids and causing local burning pain. Although enzymatically hydrolyzed collagen peptides have a low molecular weight (< 5 kDa), aminopeptidase in the vaginal environment rapidly breaks down the peptide chains, and clinical tests show that the effective residual amount is less than 15% of the initial amount after 6 hours. The core problem with these solutions is that they have not established a synergistic system for component delivery, cell activation, and structural reconstruction, and have failed to solve the stability issues of key active ingredients during preparation and use. Therefore, there is a need to design a composition that restores vaginal tightness and elasticity, and its preparation method. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, a composition for vaginal tightening and elasticity restoration and a method for preparing the same are provided.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A composition for vaginal tightening and elasticity restoration, comprising, by weight, the following components: 75-130 parts of collagen structure repair unit, 25-55 parts of composite crosslinking agent, 8-35 parts of fibroblast activating factor, and 12-38 parts of plant tannin delivery system.

[0008] The collagen structure repair unit is a hydrolyzed collagen peptide with a molecular weight of 1800-3800 Da, containing more than 7.2 wt% lysine residues and more than 9.5 wt% hydroxyproline.

[0009] The preparation method of the hydrolyzed collagen peptide includes the following steps: a) Raw material processing: Take bovine Achilles tendon tissue, immerse it in phosphate buffer containing 0.15-0.2 mol / L sodium citrate, and perform circulatory de-blooding treatment at 4°C for 180-300 minutes; b) Enzymatic hydrolysis: The tissue obtained after raw material processing is placed in a reaction vessel, and protease is added for gradient hydrolysis at 38-42℃ and pH 7.8-8.3 for 8-10 hours; c) Separation and purification: The product of the enzymatic hydrolysis reaction is separated by passing it through a 100kDa ultrafiltration membrane and a 10kDa nanofiltration membrane in sequence, and the peptide solution in the molecular weight range of 1800-3800 Da is collected. The result is hydrolyzed collagen peptide.

[0010] The protease comprises enzymes with an activity of 2.5 × 10⁻⁶. 5 U / g of Bacillus subtilis protease and enzyme activity 1.8×10 5 U / g of trypsin, wherein the mass ratio of subtilisin to trypsin is 1:0.8-1.2.

[0011] The composite crosslinking agent is formed by chemical grafting of dermatin sulfate and carboxymethyl β-glucan, and the initial mass ratio of dermatin sulfate to carboxymethyl β-glucan is 1:0.7-1.3.

[0012] The preparation method of the composite crosslinking agent includes the following steps: a) Activation of dermatin sulfate: Under a nitrogen atmosphere, dermatin sulfate is dissolved in 0.1 mol / L carbonate buffer solution, and epichlorohydrin is added, wherein the molar ratio of dermatin sulfate to epichlorohydrin is 1:2-3. The reaction is carried out at 50-58℃ for 150-210 minutes. b) Grafting reaction: Add a 12% carboxymethyl β-glucan solution to the reaction system, control the pressure of the reactor at 0.18-0.28 MPa, and heat to 58-63℃ for 4 hours to generate hybrid molecules linked by ether bonds; c) Product purification: The reaction solution obtained from the grafting reaction was dialyzed to remove free small molecules, with a molecular weight cutoff of 3.5 kDa.

[0013] The plant tannin delivery system consists of plant tannins encapsulated in a pH-responsive carrier; The method for preparing the carrier includes the following steps: a) Preparation of lipid phase: Hydrogenated lecithin, cholesterol, and stearamide were dissolved in chloroform at a mass ratio of 10:(2-3):(1-2); b) Thin film formation: Rotary evaporation removes chloroform, forming a uniform lipid film on the bottle wall; c) Hydration and dispersion: Add buffer solution containing 0.05 mol / L sodium dihydrogen phosphate, and shake in a water bath at 42-47℃ for 60-120 minutes; d) Particle size control: The particle size is circulated 5-7 times under 80-88 MPa pressure using a high-pressure micro-jet homogenizer; The plant tannins are a mixture of persimmon tannin and pomegranate ellagic acid in a mass ratio of 2-3:1, with a tannin purity ≥92%.

[0014] The preparation method of the plant tannin delivery body includes the following steps: the plant tannin is prepared into a 200 mg / mL solution, then mixed with a carrier at a volume ratio of 1:2-4, and treated with microfluidic jet at 85 MPa 5 times to obtain the plant tannin delivery body.

[0015] The fibroblast activating factor comprises copper tripeptide-1, acetyl tetrapeptide-3 and zinc ions, wherein the molar ratio of copper tripeptide-1 to acetyl tetrapeptide-3 is 1:1.3-1.9, and the concentration of zinc ions is 0.75-1.6 mmol / L.

[0016] A method for preparing a composition that tightens and restores vaginal elasticity, the method comprising the following steps: a) Mix 75-130 parts of collagen structure repair unit with 25-55 parts of composite crosslinking agent solution and stir at 500 rpm for 15 minutes; b) Add 12-38 parts of vegetable tannin delivery system and incubate at 25±2℃ for 400 seconds. -1 Homogenize the shear rate for 10 minutes; c) Slowly add 8-35 parts of fibroblast activating factor, adjust the pH value to 4.8-5.3, and obtain a gel-like composition that tightens and restores vaginal elasticity.

[0017] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. The collagen structure repair unit of this application uses hydrolyzed collagen peptides with a molecular weight within a specific narrow range. This optimization allows collagen fragments to fully penetrate into the mucosal basal layer. Controlling the molecular weight ensures that the polypeptide chain length is just right to enter the intercellular spaces of epithelial cells, while the lysine residue content is greater than 7.2 wt% and the hydroxyproline content is greater than 9.5 wt%, fundamentally solving the problem of traditional collagen's ineffective delivery.

[0018] 2. In the cross-linking system, this invention creatively combines dermatin sulfate with carboxymethyl β-glucan to form a novel composite cross-linking agent. Unlike simple physical mixing, this hybrid molecule linked by ether bonds can act on both collagen fibers and elastin simultaneously. Dermatin sulfate provides the cross-linking sites, while the grafted carboxymethyl β-glucan chains form a spatial buffer layer, enhancing tissue water retention and avoiding mucosal dehydration caused by strong astringents. Especially in physiologically acidic environments, the hydrophilic groups of this composite structure can form a hydration protective film, maintaining the microenvironment required for lactic acid bacteria growth.

[0019] 3. The intelligent delivery system for plant tannins is the key technology for overcoming the degradation of active ingredients in this invention. By constructing a lipid carrier with pH-responsive properties, persimmon tannins and pungent ellagic acid are released slowly in a specific acidic environment. The hydrogenated lecithin in the carrier forms a stable bilayer, and with the positive charge anchor provided by stearamide, it can maintain structural integrity under alkaline conditions. In the natural weakly acidic environment of the vagina, the conformation of the phospholipid molecules in the carrier changes, allowing the encapsulated tannins to be released in an orderly manner, thus solving the defect of conventional liposomes that are easily hydrolyzed and degraded in acidic environments.

[0020] 4. Regarding the promotion of tissue regeneration, the fibroblast activating factor designed in this invention employs a polypeptide-metal ion complex structure. A copper tripeptide and an acetyl tetrapeptide are coordinated in a specific molar ratio, then form a stable ternary complex with zinc ions. The zinc ions protect the peptide chain from protease cleavage while maintaining the valence state of the copper ions at the active site. When this complex comes into contact with fibroblasts, the complexed copper ions can precisely activate intracellular lysine oxidase, exhibiting superior bioavailability compared to traditional single peptides.

[0021] 5. Specific optimizations were performed at multiple stages throughout the entire preparation process. During collagen peptide extraction, a gradient-cooling enzymatic hydrolysis scheme was employed. In the grafting step of cross-linking agent synthesis, precise control of the reactor pressure and temperature ensured that the epoxy sites on each dermatan sulfate molecule could be effectively grafted with dextran.

[0022] 6. The gel matrix of the final product of this application, by adjusting the pH value within a precise weakly acidic range, both activates the carrier release system and maintains compatibility with physiological pH. This viscoelastic material not only facilitates prolonged local retention time, but its shear-thinning properties also ensure comfort during use. Detailed Implementation

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] The sources of various raw materials in this application are briefly described as follows: Sodium citrate: Purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 68-04-2, model S817548. Phosphate buffer: Purchased from Sigma-Aldrich, pH adjustment range 7.8-8.3, model P5368. Substance protease: Purchased from Sigma-Aldrich, CAS No. 9014-01-1, enzyme activity 2.5 × 10⁻⁶. 5 U / g, model number P5459. Trypsin: purchased from Beijing Solarbio Science & Technology Co., Ltd., CAS number 9002-07-7, enzyme activity 1.8×10 5U / g, model T8150. Dermatin sulfate: purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS No. 54328-33-5, model S24007. Carboxymethyl β-glucan: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., CAS No. 9041-22-7, model C815786. Epichlorohydrin: purchased from Bailingwei Technology Co., Ltd., CAS No. 106-89-8, model 800589. Carbonate buffer: purchased from Sinopharm Chemical Reagent Co., Ltd., concentration 0.1 mol / L, pH adjusted according to requirements, model CB0500. Hydrogenated lecithin: purchased from Nanjing Dulai Biotechnology Co., Ltd., CAS No. 8002-43-5, model DL03009. Cholesterol: purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 57-88-5, model C104588. Stearamide: Purchased from Saen Chemical Technology Co., Ltd., CAS No. 124-26-5, model SA8420. Chloroform: Purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 67-66-3, model 10006818. Sodium dihydrogen phosphate buffer: Purchased from Sigma-Aldrich, CAS No. 7558-80-7, concentration 0.05 mol / L, model S3139. Persimmon tannin: Purchased from Xi'an Tianyi Biotechnology Co., Ltd., CAS No. 1401-55-4, purity ≥92%, model TY0012. Pomegranate ellagic acid: Purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS No. 476-66-4, purity ≥92%, model Y2943. Copper tripeptide-1: Purchased from Shanghai Jier Biochemical Co., Ltd., CAS No. 89030-95-5, model GH1023. Acetyl tetrapeptide-3: Purchased from Zhejiang Xianju Pharmaceutical Co., Ltd., CAS No. 928006-03-1, model XJ0405. Zinc ions: Provided in the form of zinc chloride, purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 7646-85-7, model Z814021.

[0025] A composition for vaginal tightening and elasticity restoration, comprising, by weight, the following components: 75-130 parts of collagen structure repair unit, 25-55 parts of composite crosslinking agent, 8-35 parts of fibroblast activating factor, and 12-38 parts of plant tannin delivery system.

[0026] The collagen structure repair unit is a hydrolyzed collagen peptide with a molecular weight of 1800-3800 Da, containing more than 7.2 wt% lysine residues and more than 9.5 wt% hydroxyproline.

[0027] The preparation method of the hydrolyzed collagen peptide includes the following steps: a) Raw material processing: Take bovine Achilles tendon tissue, immerse it in phosphate buffer containing 0.15-0.2 mol / L sodium citrate, and perform circulatory de-blooding treatment at 4°C for 180-300 minutes; b) Enzymatic hydrolysis: The tissue obtained after raw material processing is placed in a reaction vessel, and protease is added for gradient hydrolysis at 38-42℃ and pH 7.8-8.3 for 8-10 hours; c) Separation and purification: The product of the enzymatic hydrolysis reaction is separated by passing it through a 100kDa ultrafiltration membrane and a 10kDa nanofiltration membrane in sequence, and the peptide solution in the molecular weight range of 1800-3800 Da is collected. The result is hydrolyzed collagen peptide.

[0028] The protease comprises enzymes with an activity of 2.5 × 10⁻⁶. 5 U / g of Bacillus subtilis protease and enzyme activity 1.8×10 5 U / g of trypsin, wherein the mass ratio of subtilisin to trypsin is 1:0.8-1.2.

[0029] The composite crosslinking agent is formed by chemical grafting of dermatin sulfate and carboxymethyl β-glucan, and the initial mass ratio of dermatin sulfate to carboxymethyl β-glucan is 1:0.7-1.3.

[0030] The preparation method of the composite crosslinking agent includes the following steps: a) Activation of dermatin sulfate: Under a nitrogen atmosphere, dermatin sulfate is dissolved in 0.1 mol / L carbonate buffer solution, and epichlorohydrin is added, wherein the molar ratio of dermatin sulfate to epichlorohydrin is 1:2-3. The reaction is carried out at 50-58℃ for 150-210 minutes. b) Grafting reaction: Add a 12% carboxymethyl β-glucan solution to the reaction system, control the pressure of the reactor at 0.18-0.28 MPa, and heat to 58-63℃ for 4 hours to generate hybrid molecules linked by ether bonds; c) Product purification: The reaction solution obtained from the grafting reaction was dialyzed to remove free small molecules, with a molecular weight cutoff of 3.5 kDa.

[0031] The plant tannin delivery system consists of plant tannins encapsulated in a pH-responsive carrier; The method for preparing the carrier includes the following steps: a) Preparation of lipid phase: Hydrogenated lecithin, cholesterol, and stearamide were dissolved in chloroform at a mass ratio of 10:(2-3):(1-2); b) Thin film formation: Rotary evaporation removes chloroform, forming a uniform lipid film on the bottle wall; c) Hydration and dispersion: Add buffer solution containing 0.05 mol / L sodium dihydrogen phosphate, and shake in a water bath at 42-47℃ for 60-120 minutes; d) Particle size control: The particle size is circulated 5-7 times under 80-88 MPa pressure using a high-pressure micro-jet homogenizer; The plant tannins are a mixture of persimmon tannin and pomegranate ellagic acid in a mass ratio of 2-3:1, with a tannin purity ≥92%.

[0032] The preparation method of the plant tannin delivery body includes the following steps: the plant tannin is prepared into a 200 mg / mL solution, then mixed with a carrier at a volume ratio of 1:2-4, and treated with microfluidic jet at 85 MPa 5 times to obtain the plant tannin delivery body.

[0033] The fibroblast activating factor comprises copper tripeptide-1, acetyl tetrapeptide-3 and zinc ions, wherein the molar ratio of copper tripeptide-1 to acetyl tetrapeptide-3 is 1:1.3-1.9, and the concentration of zinc ions is 0.75-1.6 mmol / L.

[0034] A method for preparing a composition that tightens and restores vaginal elasticity, the method comprising the following steps: a) Mix 75-130 parts of collagen structure repair unit with 25-55 parts of composite crosslinking agent solution and stir at 500 rpm for 15 minutes; b) Add 12-38 parts of vegetable tannin delivery system and incubate at 25±2℃ for 400 seconds. -1 Homogenize the shear rate for 10 minutes; c) Slowly add 8-35 parts of fibroblast activating factor, adjust the pH value to 4.8-5.3, and obtain a gel-like composition that tightens and restores vaginal elasticity.

[0035] The collagen structure repair unit prepared by this invention has precise membrane permeability and structural matching. The composite cross-linking agent realizes dual tissue repair function and microenvironment regulation. The pH-responsive plant tannin delivery system overcomes the problem of component degradation through intelligent controlled release. The metal ion-peptide synergistic fibroblast activating factor enhances biological stability and cell regulation efficiency. Finally, through process synergy, a triple synergistic effect of rebuilding collagen network, strengthening elastic fibers and maintaining matrix homeostasis is formed.

[0036] The technical solutions of the present invention are further illustrated below through examples and comparative examples, but the scope of protection of the present invention is not limited thereto.

[0037] Example 1 The vaginal tightening and elasticity restoration composition was prepared by the following steps: 75 parts by weight of collagen structure repair unit were used, and hydrolyzed collagen peptides with a molecular weight of 3800 Da were employed, containing 8.1 wt% lysine residues and 10.2 wt% hydroxyproline. During the preparation of this collagen peptide, bovine Achilles tendon tissue was debled in phosphate buffer containing 0.2 mol / L sodium citrate at 4°C for 180 minutes; subsequently, subtilisin and trypsin (mass ratio 1:0.8, enzyme activity both meeting limits) were added, and hydrolysis was carried out at 42°C and pH 8.3 for 8 hours; the enzymatic hydrolysate was separated by a 100 kDa ultrafiltration membrane and a 10 kDa nanofiltration membrane to obtain a peptide solution.

[0038] 55 parts by weight of the composite crosslinking agent were used, and dermatin sulfate and carboxymethyl β-glucan were added at a mass ratio of 1:0.7. Activation stage: Dermatin sulfate was reacted with epichlorohydrin (molar ratio 1:2) at 58℃ for 150 minutes under nitrogen. Grafting stage: 12% carboxymethyl β-glucan solution was added, and the reaction was carried out at 0.18 MPa and 63℃ for 4 hours. The complex was obtained after dialysis.

[0039] The plant tannin delivery system consisted of 38 parts by weight. The carrier was constructed from hydrogenated lecithin, cholesterol, and stearamide in a mass ratio of 10:3:2 and homogenized seven times under high pressure at 85 MPa. The plant tannins, specifically persimmon tannin and pungent ellagic acid, were mixed in a 2:1 ratio. During delivery system preparation, the tannins were prepared into a 200 mg / mL solution and mixed with the carrier at a volume ratio of 1:2, followed by microfluidic treatment at 85 MPa.

[0040] Eight parts by weight of fibroblast activating factor were used, with a copper tripeptide-1 to acetyl tetrapeptide-3 molar ratio of 1:1.3 and a zinc ion concentration of 1.6 mmol / L. In the composition molding stage: collagen units and cross-linking agent solution were mixed and stirred at 500 rpm; the delivery medium was added, and the mixture was incubated at 25°C for 400 s. -1 Shear homogenize; finally add activator and adjust pH to 5.0 to obtain gel product.

[0041] Example 2 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 130 parts by weight of collagen structure repair unit were prepared, with a molecular weight of 1800 Da, lysine residue content of 7.2 wt%, and hydroxyproline content of 9.5 wt%. Blood was removed for 300 minutes during preparation (buffer solution containing 0.15 mol / L sodium citrate); protease was prepared at a mass ratio of 1:1.2 and hydrolyzed at 38℃ and pH 7.8 for 10 hours.

[0042] Take 25 parts by weight of the composite crosslinking agent, with a feeding ratio of 1:1.3. Activation reaction: molar ratio 1:3, reaction at 50℃ for 210 minutes; grafting pressure 0.28 MPa, reaction at 58℃.

[0043] Twelve parts by weight of plant tannin delivery body were prepared, with a carrier-lipid ratio of 10:2:1, and homogenized at 80 MPa for 5 cycles; the tannin mixing ratio was 3:1. The volume ratio of delivery body preparation was 1:4.

[0044] Fibroblast activating factor was prepared in 20 parts by weight, with a molar ratio of 1:1.6, and zinc ions were added at a concentration of 0.75 mmol / L. The pH of the final product was adjusted to 5.3.

[0045] Example 3 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 100 units of collagen (molecular weight 2500 Da) were debled for 240 minutes (0.18 mol / L buffer); hydrolyzed at 40℃ and pH 8.0 for 9 hours with a protease ratio of 1:1.

[0046] 40 parts by weight of composite crosslinking agent, feed ratio 1:1.0. Activation: molar ratio 1:2.5, reaction at 55℃ for 180 minutes; grafting pressure 0.23 MPa, reaction at 60℃.

[0047] The delivery body was prepared in a 25-part mass ratio with a carrier-lipid ratio of 10:2.5:1.5, homogenized at 83 MPa for 6 cycles; the tannin mixing ratio was 2.5:1. The preparation volume ratio was 1:3.

[0048] The activator was 35 parts by mass, with a molar ratio of 1:1.9, and zinc ions were 1.2 mmol / L. The final product had a pH of 4.8.

[0049] Comparative Example 1 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: The molecular weight of collagen peptides is 5000 Da (out of range).

[0050] Comparative Example 2 In this comparative example, the similarities with Example 2 will not be repeated, and the differences are as follows: The composite cross-linking agent was changed to physical mixing (not chemical grafting).

[0051] Comparative Example 3 In this comparative example, the similarities with Example 3 will not be repeated, and the differences are as follows: Vegetable tannins are not encapsulated (added directly).

[0052] Comparative Example 4 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: The activator did not contain zinc ions, and the molar ratio was 1:1.

[0053] Comparative Example 5 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: The final product has a pH of 6.0 (out of range).

[0054] Performance Test Results and Analysis

[0055] Vaginal tightening and elasticity-restoring compositions were prepared according to the parameters of the examples and comparative examples, respectively. The products were tested, and the test results are shown in Table 1.

[0056] As shown in Table 1, in the mucosal permeability test, all three examples exhibited significant advantages, with mucosal permeability ranging from 38.7% to 45.1%, while Comparative Example 1 suffered a sharp drop in permeability to 12.8% due to the excessively high molecular weight of the collagen peptides. This verifies the pain point mentioned in the background art that "molecular weight > 50kDa cannot permeate the membrane." The examples, by strictly controlling the molecular weight within the 1800-3800 Da range, enabled collagen fragments to smoothly enter the intercellular spaces of epithelial cells. In particular, the best performance of 45.1% in Example 3 is closely related to its use of an intermediate molecular weight of 2500 Da to achieve spatial scale balance—ensuring both membrane permeability and maintaining sufficient three-dimensional structural integrity.

[0057] Table 1 Analysis of Test Results

[0058] Collagen regeneration rate directly reflects the core efficacy of the composition. The collagen regeneration rates of 48.9-53.6% in the examples of this application confirm the synergistic effect of the amino acid characteristics of hydrolyzed collagen peptides and the composite cross-linking agent. The comparison with Comparative Example 2, which showed only 32.8%, illustrates that physically mixed cross-linking agents cannot form a spatial buffer layer like chemically grafted products. In contrast, the hybrid molecules linked by ether bonds in the examples allow carboxymethyl β-glucan to maintain tissue moisture like a molecular sponge, supporting elastin remodeling.

[0059] The survival rate of lactic acid bacteria validated the microenvironment compatibility. The survival rate of lactic acid bacteria in all examples exceeded 92%, with Example 3 reaching 96.3%. This was attributed to the orderly release of tannins by the pH-responsive carrier in a weakly acidic environment, preventing the disruption of the bacterial community under alkaline conditions. Comparative Example 5, where the survival rate decreased to 88.6% after adjusting the pH to 6.0, confirmed this mechanism; when pH > 5.5, carrier release was inhibited, and the unreleased tannins continued to affect the microecology.

[0060] Regarding component stability, the 90-day retention rate of the examples was >89%, significantly higher than that of Comparative Example 3 (54.6%). The hydrogenated lecithin bilayer in the carrier was subjected to mild treatment below 60°C during preparation, and the temperature in all examples was controlled within the range of 45-60°C to avoid thermal degradation caused by conventional emulsification; the positive charge provided by stearamide stabilized the lipid structure during storage.

[0061] The final increase in elastic modulus is a comprehensive manifestation of the triple synergistic effect. In Comparative Example 4, the peptide chain protected by zinc ions was decomposed by aminopeptidase, while in this example, the molecular rivets formed by zinc ions both shielded the enzymatic sites and maintained the active valence state of copper ions, enabling fibroblasts to continuously activate collagen crosslinking and achieve a peak increase of 53.6%. This mechanism synergistically combines the structural reconstruction of the composite crosslinking agent and the antioxidant protection of plant tannins.

[0062] This invention solves the membrane permeation problem by designing highly active hydrolyzed collagen peptides with a Da of 1800-3800. It overcomes the synergy bottleneck by chemically grafting dermatin sulfate and carboxymethyl β-glucan to form a bifunctional cross-linking system. It innovatively uses a pH-responsive carrier to achieve intelligent controlled release of plant tannins to overcome stability defects. Furthermore, it enhances the activation efficiency of fibroblasts by using a zinc ion-mediated polypeptide complex structure.

[0063] The above description represents the preferred embodiment of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles described in the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A composition for vaginal tightening and elasticity restoration, characterized in that, The composition comprises, by weight, the following components: 75-130 parts of collagen structure repair unit, 25-55 parts of composite crosslinking agent, 8-35 parts of fibroblast activating factor, and 12-38 parts of plant tannin delivery system.

2. The composition for vaginal tightening and elasticity restoration according to claim 1, characterized in that, The collagen structure repair unit is a hydrolyzed collagen peptide with a molecular weight of 1800-3800 Da, containing more than 7.2 wt% lysine residues and more than 9.5 wt% hydroxyproline.

3. The composition for vaginal tightening and elasticity restoration according to claim 2, characterized in that, The preparation method of the hydrolyzed collagen peptide includes the following steps: a) Raw material processing: Take bovine Achilles tendon tissue, immerse it in phosphate buffer containing 0.15-0.2 mol / L sodium citrate, and perform circulatory de-blooding treatment at 4°C for 180-300 minutes; b) Enzymatic hydrolysis: The tissue obtained after raw material processing is placed in a reaction vessel, and protease is added for gradient hydrolysis at 38-42℃ and pH 7.8-8.3 for 8-10 hours; c) Separation and purification: The product of the enzymatic hydrolysis reaction is separated by passing it through a 100kDa ultrafiltration membrane and a 10kDa nanofiltration membrane in sequence, and the peptide solution in the molecular weight range of 1800-3800 Da is collected. The result is hydrolyzed collagen peptide.

4. The composition for vaginal tightening and elasticity restoration according to claim 3, characterized in that, The protease comprises enzymes with an activity of 2.5 × 10⁻⁶. 5 U / g of Bacillus subtilis protease and enzyme activity 1.8×10 5 U / g of trypsin, wherein the mass ratio of subtilisin to trypsin is 1:0.8-1.

2.

5. The composition for vaginal tightening and elasticity restoration according to claim 1, characterized in that, The composite crosslinking agent is formed by chemical grafting of dermatin sulfate and carboxymethyl β-glucan, and the initial mass ratio of dermatin sulfate to carboxymethyl β-glucan is 1:0.7-1.

3.

6. The composition for vaginal tightening and elasticity restoration according to claim 5, characterized in that, The preparation method of the composite crosslinking agent includes the following steps: a) Activation of dermatin sulfate: Under a nitrogen atmosphere, dermatin sulfate is dissolved in 0.1 mol / L carbonate buffer solution, and epichlorohydrin is added, wherein the molar ratio of dermatin sulfate to epichlorohydrin is 1:2-3. The reaction is carried out at 50-58℃ for 150-210 minutes. b) Grafting reaction: Add a 12% carboxymethyl β-glucan solution to the reaction system, control the pressure of the reactor at 0.18-0.28 MPa, and heat to 58-63℃ for 4 hours to generate hybrid molecules linked by ether bonds; c) Product purification: The reaction solution obtained from the grafting reaction was dialyzed to remove free small molecules, with a molecular weight cutoff of 3.5 kDa.

7. The composition for vaginal tightening and elasticity restoration according to claim 1, characterized in that, The plant tannin delivery system consists of plant tannins encapsulated in a pH-responsive carrier; The method for preparing the carrier includes the following steps: a) Preparation of lipid phase: Hydrogenated lecithin, cholesterol, and stearamide were dissolved in chloroform at a mass ratio of 10:(2-3):(1-2); b) Thin film formation: Rotary evaporation removes chloroform, forming a uniform lipid film on the bottle wall; c) Hydration and dispersion: Add buffer solution containing 0.05 mol / L sodium dihydrogen phosphate, and shake in a water bath at 42-47℃ for 60-120 minutes; d) Particle size control: The particle size is circulated 5-7 times under 80-88 MPa pressure using a high-pressure micro-jet homogenizer; The plant tannins are a mixture of persimmon tannin and pomegranate ellagic acid in a mass ratio of 2-3:1, with a tannin purity ≥92%.

8. The composition for vaginal tightening and elasticity restoration according to claim 7, characterized in that, The preparation method of the plant tannin delivery body includes the following steps: the plant tannin is prepared into a 200 mg / mL solution, then mixed with a carrier at a volume ratio of 1:2-4, and treated with microfluidic jet at 85 MPa 5 times to obtain the plant tannin delivery body.

9. The composition for vaginal tightening and elasticity restoration according to claim 1, characterized in that, The fibroblast activating factor comprises copper tripeptide-1, acetyl tetrapeptide-3 and zinc ions, wherein the molar ratio of copper tripeptide-1 to acetyl tetrapeptide-3 is 1:1.3-1.9, and the concentration of zinc ions is 0.75-1.6 mmol / L.

10. A method for preparing a composition having vaginal tightening and elasticity-restoring properties as described in any one of claims 1-9, characterized in that, The preparation method includes the following steps: a) Mix 75-130 parts of collagen structure repair unit with 25-55 parts of composite crosslinking agent solution and stir at 500 rpm for 15 minutes; b) Add 12-38 parts of vegetable tannin delivery system and incubate at 25±2℃ for 400 seconds. -1 Homogenize the shear rate for 10 minutes; c) Slowly add 8-35 parts of fibroblast activating factor, adjust the pH value to 4.8-5.3, and obtain a gel-like composition that tightens and restores vaginal elasticity.